Targeting the RANKL/RANK/OPG Axis for Cancer Therapy - Ming, Jie; Cronin, Shane J. F.; Penninger, Josef M. (Frontiers in Oncology, 2020)
RANKL and RANK are expressed in a variety of cells and tissues throughout the body. They were originally described for their key roles in bone remodeling and the immune system but have subsequently been shown to provide essential signals from regulating mammary gland homeostasis during pregnancy to modulating tumorigenesis. The success of RANKL/RANK research serves as a paragon for translational research from the laboratory to the bedside. Case in point has been the development of denosumab, a RANKL-blocking monoclonal antibody which has already helped millions of patients suffering from post-menopausal osteoporosis and skeletal related events in cancer. Here we will provide an overview of the pathway from its origins to its clinical relevance in disease with a special focus on emerging evidence demonstrating the therapeutic value of targeting the RANKL-RANK pathway not only in breast cancer but also as an addition to the cancer immunotherapy arsenal.